Retroreflective optical immunosensing based on the biospecific particle movement and time-lapse imaging in microchannel - Lee, Kyung Won; Jeong, Kwan Young; Kim, Ka Ram; Chun, Hyeong Jin; Yoon, Hyun C. (23rd International Conference on Miniaturized Systems for Chemistry and Life Sciences, MicroTAS 2019, 2019)
We developed a wash-free biosensor enabling quantitative analysis of cardiac troponin I (cTnI) using retroreflective Janus particle (RJP) as an optical probe. The RJP, we developed, had a metal layer which composed of a high refractive metal in half of the surface to induce the retroreflective phenomenon. Because of the hemisphere of the metal layer, the RJPs were sedimented and twinkled in biosensing microchannel. By using these two properties of RJP, the wash-free optical immunosensor was developed. The performance of the developed sensor was demonstrated via quantitative analysis of serum cTnI.
Keywords: Cardiac troponin I; High refractive; Immunosensing; Janus particles; Optical immunosensors; Optical probe; Particle movement; Time-lapse imaging; Non-spectroscopic; Optical Biosensor; Retroreflective Janus Particle; Wash-free Biosensor